2022
DOI: 10.1002/smll.202107104
|View full text |Cite
|
Sign up to set email alerts
|

Strain‐Plasmonic Coupled Broadband Photodetector Based on Monolayer MoS2

Abstract: Abstract2D Semiconductors are promising in the development of next‐generation photodetectors. However, the performances of 2D photodetectors are largely limited by their poor light absorption (due to ultrathin thickness) and small detection range (due to large bandgap). To overcome the limitations, a strain‐plasmonic coupled 2D photodetector is designed by mechanically integrating monolayer MoS2 on top of prefabricated Au nanoparticle arrays. Within this structure, the large biaxial tensile strain can greatly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 32 publications
(52 reference statements)
1
27
0
Order By: Relevance
“…Moreover, D* is another key parameter that quantitatively evaluates the capability to detect weak light. Assuming that the dark current is dominated by shot noise and at a bandwidth of 1 Hz, [ 20 ] D* is defined as: [ 32,33 ] Dbadbreak=A R/2qIdark\[ \begin{array}{*{20}{c}}{{D^ * } = \sqrt A \;R/\sqrt {2q{I_{{\rm{dark}}}}} }\end{array} \] where A , I dark , R , and q represent the heterostructure area, dark current, responsivity, and unit charge, respectively. Accordingly, D* values were calculated, as shown in Figure 3c,d.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, D* is another key parameter that quantitatively evaluates the capability to detect weak light. Assuming that the dark current is dominated by shot noise and at a bandwidth of 1 Hz, [ 20 ] D* is defined as: [ 32,33 ] Dbadbreak=A R/2qIdark\[ \begin{array}{*{20}{c}}{{D^ * } = \sqrt A \;R/\sqrt {2q{I_{{\rm{dark}}}}} }\end{array} \] where A , I dark , R , and q represent the heterostructure area, dark current, responsivity, and unit charge, respectively. Accordingly, D* values were calculated, as shown in Figure 3c,d.…”
Section: Resultsmentioning
confidence: 99%
“…33 Based on a previous study that showed wrinkling of monolayer MoS 2 by strain relief of a prestrained elastomer substrate did not increase the carrier mobility, 53 we believe that the strain-induced mobility enhancement effect would not be evident in our system. Because 2D semiconductors typically generate more photoelectrons when light absorption is higher, 22,54,55 we expected that the photoresponsivity of the MoS 2 layer would be higher when the number of wrinkle generations increases. Figures 3g and S6 show the spectral photoresponsivities (R) of the samples at a constant optical power density (P ≈ 10 μW cm −2 , light exposure time: 30 s).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Because 2D semiconductors typically generate more photoelectrons when light absorption is higher, ,, we expected that the photoresponsivity of the MoS 2 layer would be higher when the number of wrinkle generations increases. Figures g and S6 show the spectral photoresponsivities ( R ) of the samples at a constant optical power density ( P ≈ 10 μW cm –2 , light exposure time: 30 s).…”
Section: Resultsmentioning
confidence: 99%
“…[12,14,170,180,184] The spectral range of LSPR is closely related to the shape and size of core materials, and the curvature has modulation effect on the band structure of nanoshells. [64,[185][186][187] This provides an important reference for broadband optoelectronics (Figure 9k). [177] The situation of nanoshells is altered when noble metal NP cores are replaced by dielectric materials with high refractive index, such as Si.…”
Section: Properties and Potential Applicationsmentioning
confidence: 99%
“…[16,32,60] Second, these novel architectures, different from 2D topology, as a powerful light-matter interaction platform, induce new strong coupling modes (e.g., exciton-polaritons, plasmon-excitons) through WGM mode and Mie resonator, relying on high refractive index medium for multiple scattering and total internal reflection. [14,91,122,187] The mode strength and coupling strength also strongly depend on the size contribution. This is beneficial to function diversification, including advanced plasmonics, construction of room-temperature polaritonic devices, optical switches, and tunable lasers.…”
Section: Experimental Exploration Of Size-dependent Propertiesmentioning
confidence: 99%